2005
DOI: 10.1177/0891988705276060
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Anxiety and Depression in Older Adults: Clinical Characteristics and Management

Abstract: The frequent comorbidity of anxiety and depression, particularly among elderly, is widely recognized by clinicians, but the debate continues as to whether the combined diagnostic designation is merited. This article reviews the debate over the mixed diagnosis, discusses treatment implications, and reviews a small treatment study undertaken with elderly patients. Ten community-dwelling, older adults diagnosed with generalized anxiety disorder and subsyndromal depression (n = 6) or generalized anxiety disorder a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Additionally, the participants' depression was also assessed by the Beck Depression Inventory (BDI scores 10 or more) before inclusion. Because of the frequent comorbidity of depression and anxiety (Aina & Susman, 2006;Cassidy, Lauderdale, & Sheikh, 2005), patients with anxiety were also included (72% of the patients were diagnosed as suffering from mild, moderate or severe anxiety). Participants were included irrespective of medication status and were allowed to continue their medication regimen during the study.…”
Section: Participantsmentioning
confidence: 99%
“…Additionally, the participants' depression was also assessed by the Beck Depression Inventory (BDI scores 10 or more) before inclusion. Because of the frequent comorbidity of depression and anxiety (Aina & Susman, 2006;Cassidy, Lauderdale, & Sheikh, 2005), patients with anxiety were also included (72% of the patients were diagnosed as suffering from mild, moderate or severe anxiety). Participants were included irrespective of medication status and were allowed to continue their medication regimen during the study.…”
Section: Participantsmentioning
confidence: 99%
“…In the diagnosis of MDD, if the comorbidity pattern of anxiety and depression is taken into account based on the diagnostic criteria, MDD can be classified into the following three cases [33, 34]: 1) one where MDD and anxiety disorder are both clearly diagnosed (co-existing MDD and anxiety disorder), 2) one accompanied by anxiety satisfying the diagnostic criteria of MDD but not satisfying the diagnostic criteria of anxiety disorder (MDD + subsyndromal anxiety disorder), and 3) one where the symptoms do not satisfy the diagnostic criteria of either MDD or anxiety disorder (subsyndromal depression and anxiety disorder). To make up for the shortcomings of MDD classification using this syndromal approach, scales should be used to measure the severity of symptoms at the subsyndromal level.…”
Section: Discussionmentioning
confidence: 99%
“…Lenze et al [19] reported favorable outcomes for depressed older adults with comorbid anxiety symptoms; participants were treated in a specialty psychiatry clinic, and those with severe anxiety received lorazepam in addition to nortriptyline or paroxetine. Two small, open-label studies specifically examined antidepressant medications' efficacy for community-dwelling older adults with GAD and comorbid major depressive disorder or subsyndromal depressive symptoms; these studies suggest promise for nefazodone [20] and escitalopram [21] in treating comorbid late-life depression and anxiety.…”
Section: Treatment Considerationsmentioning
confidence: 99%